Language Style in the Novel a Big Plan to Die Quietly Works of Vishnu Suryaning Adji Stillistic Study - Hutagalung, Renaldi; Ritonga, Parlaungan; Harahap, Nurhayati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
One of the ways authors express literary works is through the use of language styles. Language style has a function that can influence the reader which can make the reader interested in what the author conveys. This research is entitled "Language Style in the novel Big Plan to Die with Calm by Wisnu Suryaning Adji". The purpose of this study is to describe the use of style in hyperbole, irony, and personification in the novel The Great Plan to Die with Tranquility by Wisnu Suryaning Adji. The method used in this study is qualitative descriptive. Based on the results of the study, the author uses hyperbolic language style to emphasize excess, describe emotional tension, create dramatic effects, give an impression of humor. The use of ironic language styles for the contrast between hope and reality, dissatisfaction and frustration, social criticism, emotional reflection, and gives a more complex layer of meaning. Using his own personification language style, the author aims to bring objects and concepts to life, create an emotional impression, add aesthetic beauty to the novel Big Plan to Die with Tenang by Wisnu Suryaning Adji.